Carbon dioxide sensing : fundamentals, principles, and applications - Gerlach, Gerald; Guth, Ulrich; Oelssner, Wolfram (Wiley-VCH Verlag GmbH, 2019)
The book provides the reader with a profound knowledge of basic principles, properties and preferred applications of diverse kinds of CO2 measurement. It shows the advantages, disadvantages and limitations of several methods and gives a comprehensive overview of both possible applications and corresponding boundary conditions. Applications reach from environmental monitoring to safety control to biotechnology and food control and finally to medicine.